Thermogravimetric study of Chlorella vulgaris for syngas production - Raheem, A.; Sivasangar, S.; Wan Azlina, W.; Taufiq Yap, Y.; Danquah, Michael; Harun, R. (2015)
The present study investigates the thermal degradation behavior of Chlorella vulgaris using a thermogravimetric analyzer (TGA) to explore application as feedstock for syngas production. The biomass was heated continuously from room temperature to 1000°C at different heating rates (5, 10 and 20°Cmin-1) under N2/air conditions at a constant flow rate of 25mLmin-1. Experimental results showed that the combustion process of C. vulgaris can be divided into three major phases; (1) moisture removal, (2) devolatilization of carbohydrates, protein and lipids and (3) degradation of carbonaceous material. A degradation rate of 80% was obtained at the second phase of the combustion process in the presence of air whilst a degradation rate of 60% was obtained under N2 atmosphere at the same phase. The biomass was further gasified for syngas production using a Temperature Programmed Gasifier (TPG). The effect of three different process variables, temperature, microalgal loading, and heating rate was investigated. The maximum H2 production was found at 800°C temperature with a biomass loading of 0.5g. No significant effect of heating rate was observed on H2 production. The activation energy values, based on the Kissinger method, were evaluated to be 45.38±0.5kJmol-1 (1st stage), 61.20±0.5 kJ mol-1 (2nd stage) and 97.22±0.5 kJ mol-1 (3rd stage). The results demonstrate a significant potential for the utilization of the microalgae biomass as feedstock for large-scale production of syngas via gasification.